The efficacy of Salvadora persica extract in the elimination of the intracanal smear layer: A SEM study - Hanan Balto; Basma Ghandourah; Hala Al-Sulaiman (Saudi Dental Journal)
Aim: To evaluate the efficacy of an ethanolic Salvadora persica extract in removing the smear layer following a root canal procedure. Methods: Sixty extracted, single-rooted human teeth were cleaned, shaped, and divided into four groups. Experimental groups 1 (n = 20) and 2 (n = 20) were irrigated with 1 mg/ml and 5 mg/ml of S. persica, respectively. The positive controls (n = 10) were irrigated with 17% ethylenediaminetetraacetic acid (EDTA), while the negative controls (n = 10) were irrigated with saline. Approximately 5 ml of the irrigating solution was delivered into the root canals for 5 min, and the final rinse was performed with 5 ml of 1% sodium hypochlorite. Scanning electron microscopy was used to evaluate the endodontic smear layer removal at the coronal, middle, and apical thirds of the specimens. Results: A significant difference in smear layer removal between groups 1 and 2 at the coronal and middle thirds of the canal was observed, and no significant difference was seen between group 2 and the positive control at the coronal third. At the apical third, both concentrations of S. persica had similar effects and were less effective than the positive control in removing the smear layer. Conclusion: The 5 mg/ml S. persica solution was significantly more effective than the 1 mg/ml solution. In addition, the 5 mg/ml S. persica solution was as effective as 17% EDTA in removing the smear layer from the coronal third of the canal wall. Keywords: EDTA, Irrigation, Smear layer, Salvadora persica